2020
DOI: 10.3897/zookeys.972.52853
|View full text |Cite
|
Sign up to set email alerts
|

Systematic revision of the genus Peronia Fleming, 1822 (Gastropoda, Euthyneura, Pulmonata, Onchidiidae)

Abstract: The genus Peronia Fleming, 1822 includes all the onchidiid slugs with dorsal gills. Its taxonomy is revised for the first time based on a large collection of fresh material from the entire Indo-West Pacific, from South Africa to Hawaii. Nine species are supported by mitochondrial (COI and 16S) and nuclear (ITS2 and 28S) sequences as well as comparative anatomy. All types available were examined and the nomenclatural status of each existing name in the genus is addressed. Of 31 Peronia species-group names avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 116 publications
(345 reference statements)
1
1
0
Order By: Relevance
“…In Hong Kong, Britton [65] recorded four species, namely Peronia verruculata, Paraonchidium reevesii, Platevindex mortoni and Onchidium hongkongense. As previously mentioned, a revision on the taxonomy of this family is being carried out by Dayrat et al [44][45][46][66][67][68][69], and found that P. reevesii, O. hongkongense, and some of the P. verruculata in [65] are actually Paromoionchis tumidus [44,66]. Our molecular analyses revealed six species of Onchidiidae in Hong Kong (Table 1).…”
Section: Family Onchidiidae (Gastropoda)supporting
confidence: 50%
“…In Hong Kong, Britton [65] recorded four species, namely Peronia verruculata, Paraonchidium reevesii, Platevindex mortoni and Onchidium hongkongense. As previously mentioned, a revision on the taxonomy of this family is being carried out by Dayrat et al [44][45][46][66][67][68][69], and found that P. reevesii, O. hongkongense, and some of the P. verruculata in [65] are actually Paromoionchis tumidus [44,66]. Our molecular analyses revealed six species of Onchidiidae in Hong Kong (Table 1).…”
Section: Family Onchidiidae (Gastropoda)supporting
confidence: 50%
“…Some adapted to distinct microhabitats within riverine mangrove forests, including silty muds ( Alionchis , Laspionchis , Paromoionchis , and Peronina ) 57 , 59 , 61 , 62 , mounds of mud and dead logs ( Onchidium ) 50 , 51 , roots and trunks of mangrove trees ( Melayonchis and Platevindex ) 52 , 54 , 55 , and supratidal fringes of mangroves ( Onchidina ) 56 . Other onchidiids diversified in coastal, fringe forests with sand and coral rubble ( Wallaconchis ) 58 or transitioned back to the rocky intertidal ( Peronia, Marmaronchis , and Wallaconchis ) 53 , 58 , 60 . The association of onchidiids with rocky intertidal habitats is not phylogenetically constrained, with none of these three genera being sister-taxa, and all being highly diverged from the genus Onchidella, which also inhabits rocky shores at the margins of the Indo-West Pacific 46 .…”
Section: Resultsmentioning
confidence: 99%